Improving the starting torque and overall efficiency of split single phase induction motor - Mohamed Adel Esmaeel Salama; Wael Mohamed Fayek Abdel-Karim (Institute of Advanced Engineering and Science, 2023)
Single-phase split induction motors consist of an auxiliary coil, a main winding and a centrifugal switch that separates the auxiliary coil. The starting torque of this motor is not large, and a resistance has to be added with the additional coil to increase the starting torque. Also, a mechanical centrifugal switch is used to disconnect the auxiliary coil. The motor also has another drawback that it has a constant speed. The aim of this research is to replace the added resistance with a current transformer that has a predetermined resistance and connected in series with the auxiliary coil such that it results in a maximum starting torque. In addition, it sends a signal to a control circuit that disconnect/connect the auxiliary coil through an electronic switch connected in series with the auxiliary coil. The connection/disconnection of the switch depends on the motor current not the motor speed to overcome the problem of switch false triggering due to motor overloading. The new technique increases the overall efficiency of the motor. MATLAB is used to simulate the system and verify the mathematical model.